Introduction pages, Nova Geodesia 2(1), 2022 - Paul SESTRAS (Nova Geodesia, 2022)
Nova Geodesia (https://novageodesia.ro), Issue 1, Volume 2, 2022: The papers published in this issue represent interesting novelties in different topics of geodetic science. Among the exciting articles, we invite readers to find news about: Documenting 20th and 21st century glacier change and landscape evolution with maps and land, aerial, and space-based geospatial imagery in Alaska’s Kenai Mountains; Wintering habitat modelling for conservation of Eurasian vultures in northern India; Spatial data acquisition for traffic lights intersections as a basis for GIS development in Timisoara, Romania.